(untitled) (Minerva, 2019)
In this paper we analize the metrical inscriptions from Argolis prior to ca. 400 a. C. Although the influence of Ionian poetry is pervasive, the dialectal features in these documents match those appearing in contemporary prose inscriptions. Contrary to some previous research, we conclude that the epigrams from Argolis do not deliberately avoid using the local dialect.